Neural reprogramming via microRNAs: the new kid on the p53-deficient block - Deborah A. Silverman; George A. Calin; Jeffrey N. Myers; Moran Amit (Molecular & Cellular Oncology, 2020)
We recently reported a novel role for nerve-cancer crosstalk, demonstrating that tumor protein p53 (TP53) deficiency in head and neck squamous cell carcinoma leads to a decrease in miR-34a in tumor-shed vesicles. This directed sensory nerve reprogramming in the tumor microenvironment which enhanced tumor growth.